Mass communication yearbook - Michael Gurevitch; Mark R. Levy (Sage Publications, 1985)
Mass communication review Yearbook 5 presents the best in recent mass communication research on new development in the field , mass media and society, mass media and the individual, and mass communication technology and policy.